MANETs performance analysis with dos attack at different routing protocols - Zain, Alaa; El-khobby, Heba; M. Abd Elkader, Hatem; Abdelnaby, Mostafa (International Journal of Engineering and Technology, 2015)
A Mobile Ad-Hoc Networks (MANET) is widely used in many industrial and people's life applications, such as earth monitoring, natural disaster prevention, agriculture biomedical related applications, and many other areas. Security threat is one of the major aspects of MANET, as it is one of the basic requirements of wireless sensor network, yet this problem has not been sufficiently explored. The main purpose of this paper is to study different MANETs routing protocols with three scenarios of Denial of Service (DoS) attacks on network layer using proactive routing protocol i.e. Optimized Link State Routing (OLSR) and Reactive routing protocols like Ad hoc On-Demand Distance Vector (AODV), Hybrid routing protocols like Geographic Routing Protocol (GRP). Moreover, a comparative analysis of DoS attacks for throughput, Data loss, delay and network load is taken into account. The performance of MANET under the attack is studied to find out which protocol is more vulnerable to the attack and how much is the impact of the attack on both protocols. The simulation is done using OPNET 17.